Analisis Kepuasan Pengguna Aplikasi Mobile JKN di BPJS Kesehatan Kantor Cabang Magelang - Wigatie, Ragil Ayu; Zainafree, Intan (Poltekkes Kemenkes Kendari, 2023)
Optimizing the digitization of public services is one of the essential factors in creating community satisfaction as service users. As a fulfillment of the commitment to JKN-KIS participants, BPJS Kesehatan has developed various innovations based on information technology. The JKN Mobile Application is a form of digital transformation in which administrative services at branch offices and health facilities can now be accessed anywhere and without time limits. The aim of this research is to assess how contented JKN members in the BPJS Kesehatan KC Magelang region are with the Mobile JKN app. This study uses a quantitative descriptive method. The population studied was JKN-KIS participants who had registered in the Mobile JKN application and were domiciled in the work area of ??the BPJS Kesehatan KC Magelang, then 100 samples were selected using a purposive sampling technique and distributing questionnaires with a Likert scale as a data collection technique. The variable used is End User Computing Satisfaction (EUCS) which consists of Content, Accuracy, Format, Ease of Use, and Timeliness, with user satisfaction as the dependent variable. The study results show that most (69%) of respondents are satisfied with digitizing services through the Mobile JKN application. Users' satisfaction with the Mobile JKN application organized by BPJS Kesehatan KC Magelang was found to increase with each of the investigated variables.